(untitled) - Burgess, Sally (Harlow, England, 2005)
The How to!series offers practical teaching ideas within a clear, theoretical framework. Each title includes a photocopiable 'Task File' of training and reflection activities to reinforce the theories and practical ideas presented. An analysis of how listening, speaking, reading and writing, as well as grammar and vocabulary, are tested in a range of exams, and a description of appropriate teaching strategies for each. A guide to all the major international English language exams and information on how to keep up-to-date with changes to these exams.
Keywords: English language,English teachers,English language,Ngôn ngữ tiếng Anh,Ngôn ngữ tiếng Anh; Study and teaching,Training of self studying,Teacher training,Dạy và học,Đào tạo giáo viên